Farmer’s perception and adaptation strategies to climate change on potato farming in Narayan Municipality of Dailekh district, Nepal - Budhathoki, Prabina; Thapa, Dristi; Khadka, Dibash; Khatri, Namuna (Archives of Agriculture and Environmental Science, 2025)
This study was aimed to assess farmer’s perceptions of climate change and their adaptations in potato farming in Dailekh District, Nepal. A total of 97 randomly selected respondents were selected for the study. Primary data was collected through focus group discussions, direct observation, semi-structured questionnaires while secondary data was collected through review of relevant literature. The data was analyzed using descriptive statistics, time series regression, Logit, and Seemingly Unrelated Regression model (SUR). By analyzing the farmer perception of climate change, 75.26% of the respondent experience climate change. In contrast to 84.5% farmer perceived increased temperature, 94.85% believed decrease rainfall duration with increase in rainfall intensity. The key variables determining the climate change perception of farmer were: socio-economic variables (education, farming experience, and family size) and bio-physical variables (increase in drought, change in insect pests and diseases and lack of irrigation). Based on the study, 58.76% of the farmers adopted climate adaptations. Farmers primarily adapted to climate change through changing potato variety (61.86%), adjusting planting/harvesting time (64%), changing planting method (71.13%), pest’s management, irrigation, fertilizers, and crop rotation. Logistic regression revealed higher education and attainment of training increased adaptation by 9% and 18.54%, respectively. A link was found between farmers’ perception of climate change and the implementation of some adaptation options. Thus, socioeconomic and biophysical variables have a significant association with adaptation, as well as investment in education, extension training, and access to credit, and can be considered to increase climate change adaptation to improve farmers’ well-being.